Trust, Value, Price Fairness: Boosting Loyalty in Eco Hair Care - Dinanti, Altisya Putri; Suhud, Usep; Krissanya, Nofriska (LPPPIPublishing, 2024)
The purpose of this research is to determine the influence of trust, perceived value, perceived price fairness, and customer satisfaction on customer loyalty to environmentally friendly hair care products. The research method uses a quantitative research design by distributing questionnaires. A total of 254 respondents were sampled using purposive sampling technique. The research objects in this study were respondents aged 18-60 years in DKI Jakarta and had purchased environmentally friendly hair care products at least three times in the last year. This research uses SPSS version 26 software and SEM (Structural Equation Model) from AMOS software to analyze and process research data. The research results show that: first, trust, perceived value, and perceived price fairness have a positive and significant effect on customer satisfaction. Second, trust, perceived value, and customer satisfaction have a positive and significant effect on customer loyalty. Third, perceived price fairness has no influence on customer loyalty.